2018
DOI: 10.3389/fphar.2018.00095
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol Inhibits Oxidized Low-Density Lipoprotein-Induced Vascular Endothelial Cells Autophagy by Upregulating the Expression of miRNA-30a

Abstract: Paeonol from Cortex Moutan root is a potential therapeutic agent for atherosclerosis (AS). However, its mechanisms of action are still not fully understood. Vascular endothelial cells (VECs) autophagy plays a vital role in the initiation and progression of AS. In this study, we aim to investigate whether the protective effect of paeonol on ox-LDL-induced VECs injury by regulating autophagy. To address this question, we used ox-LDL-induced rat VECs as a model system to elucidate the protective effect of paeonol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…HEK-293T cells (human embryonic kidney-293 cells expressing the large T-antigen of simian virus 40) were purchased from the cell bank of Chinese Academy of Sciences and cultured in DMEM-HG supplemented with 10% FBS, 100 U/ml penicillin, and 100 μg/ml streptomycin. Vascular endothelial cells (VECs) were isolated from the abdominal aortic of SD rats as previously described [ 22 ] and cultured in DMEM-HG complete medium. Finally, these cells were digested and passaged when reaching 80% of confluence.…”
Section: Methodsmentioning
confidence: 99%
“…HEK-293T cells (human embryonic kidney-293 cells expressing the large T-antigen of simian virus 40) were purchased from the cell bank of Chinese Academy of Sciences and cultured in DMEM-HG supplemented with 10% FBS, 100 U/ml penicillin, and 100 μg/ml streptomycin. Vascular endothelial cells (VECs) were isolated from the abdominal aortic of SD rats as previously described [ 22 ] and cultured in DMEM-HG complete medium. Finally, these cells were digested and passaged when reaching 80% of confluence.…”
Section: Methodsmentioning
confidence: 99%
“…Exosomes can be used not only as a marker of disease diagnosis, drug targeting transport carrier, is also expected to become a therapeutic target for diseases ( Milane et al, 2015 ; Zhang et al, 2015 ; Suchorska and Lach, 2016 ). Several studies showed that miR-223 could transfer from monocytes to vascular cells by means of exosomes and play a pivotal role in normal physiological processes and pathological processes of AS ( Cheng et al, 2017 ; Li et al, 2018 ; Liu et al, 2018 ). The miR-223 overexpression significantly attenuated macrophage foam cell formation, lipid accumulation and pro-inflammatory cytokine production ( Bao et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Paeonol has a good transdermal absorption, which is suitable for oral direct administration. Moreover, Paeonol has been applied for its anti-inflammatory, antioxidant, and antibacterial properties for a long time in traditional Chinese medicine [26,27,28].…”
Section: Discussionmentioning
confidence: 99%